THE PHYSICAL AND CHEMICAL CHARACTERIZATION OF SOME GROUND AND SURFACE WATERS IN SAO PAULO STATE, BRAZIL - Bonotto, Daniel Marcos (2010)
For many years, environmentalists, humanitarians, government agencies, politicians, educators, and others have expressed the concern for protecting the hydrological resources against pollutants. Sao Paulo is the most populous Brazilian state, comprising 40 million inhabitants distributed over 645 municipalities. It has the highest number of industries and economic production, reaching 31% of the Brazilian GDP-gross domestic product. Despite the vigorous industrial production that includes high technology goods, the state also is well developed in agriculture and cattle breeding. This advanced stage of agricultural and industrial growth causes to Sao Paulo State a great diversity of problems related to the interaction between the society and the environment. The fats, oil and grease (FOG), nitrate, sulfate, sodium hydroxide among other chemicals have constituted important source of contaminants to the hydrologic environment in Sao Paulo State. The disposal of vinasse, the major effluent from the ethanol industry, has represented a major environmental problem at Sao Paulo State. The number of gas stations suppliers at Sao Paulo State corresponds to 7500 that is significant if compared with 28500 existing in Brazil. They must provide fuel to about 15 million vehicles in Sao Paulo State, but such number is increasing, for instance, raised 26% from 2002 to 2006. Therefore, FOG releases to groundwater associated to gas stations suppliers also constitute an important environmental question to be solved by Sao Paulo State authorities. This chapter shows how different techniques can be utilized to investigate the water quality in different hydrographic basins in Sao Paulo State, Brazil. Particular attention is directed for describing the importance of some chemicals on the contamination of underground and surface waters. The major anthropogenic factors responsible by the pollution are also taken into account, as well the major natural water-rock interaction processes responsible by the transfer of elements/compounds to the liquid phase, mainly in sites where the hydrological resources are used in public water-supply systems.